Psikoedukasi Implementasi Pencegahan Bunuh Diri Remaja dalam Lingkup Keluarga - Dina Vebiana; Immanuela Andieny M. I. Sitanggang; Anisa Sulistya Nindita (Devotion : Jurnal Pengabdian Psikologi, 2022)
The importance of suicide problem in adolescent problem is becoming one of the cause of death in individuals aged 15 through 29, Therefore, a preventive measure is needed to prevent this problem, the focus of this community development program is family based intervention targeted to parents of 9th grade students in 1 Taman Public Middle School. Community development program was held through a workshop filled with materials and roleplay. Most of the participants have the interest in regards to the problem presented but have a lack of knowledge and skills in regards to suicide, this is presented through a less applicative answer during the roplay session. Therefore, it is necessary to have periodic training with the same topic.